An Ecological Appraisal of Reclaimed Limestone mines in Mussoorie hills, India - Dangayach, Ruchi; Bhandari, Saumya; Sivaranjani, S.; Pal Panwar, Vijender; Bala, Nirmalaya (Indian Forester, 2022)
The present study investigates the floral diversity of reclaimed limestone mined areas in Lambidehar and Chunakhala and the changes brought about in the associated soils. Soil eco-physiological indicators and floral diversity of the sites were studied using quadrat analysis, which revealed that the reclaimed mine areas display a dynamic floral community and a steady soil improvement. The density and abundance showed a declining trend with time which may be attributed to the anthropogenic disturbances evident during the study. Species diversity was greater in Chunakhala as compared to Lambidehar where the index values for different vegetation forms are comparable with the values of other Himalayan forest (0-3.037). The diversity indices of shrubs at Chunakhala were higher, along with a higher total basal area. The soil physical properties such as bulk density have improved over the years, whereas soil texture remains the same (sandy loam). The chemical properties improved over the years because of the deposition of organic matter due to the higher shrubs and herbs population, contributing a significant amount of litter from both top growth and roots. Both the mine sites reclaimed significantly, and primary colonizing plant species grew well on the earlier derelict sites.